Inflammatory myofibroblastic tumor of the sigmoid colon: A case report - Suleiman Ayalew; Michael A. Negussie; Messay Gebrekidan; Dinksira Bekele Deneke; Mulat Asrade Alemayehu; Mesfin Tesera Wassie (Journal of Pediatric Surgery Case Reports, 2025)
Introduction: Inflammatory myofibroblastic tumors (IMTs) are rare tumors primarily affecting children and young adults. IMT of the sigmoid colon is particularly rare, with very few cases reported in the literature. Case presentation: A 2-year-old boy presented with a three-month history of painless, progressive abdominal swelling that began in the right lower abdomen and extended across to the left. He also experienced significant weight loss and reduced appetite, though there were no symptoms of nausea, vomiting, diarrhea, constipation, or rectal bleeding. On examination, a 10 cm firm, non-tender, and non-mobile mass was noted in the right lower quadrant and hypogastric region. No other abnormalities were detected. Laboratory results revealed severe anemia (hemoglobin: 6.1 g/dL) and elevated white blood cell (17,400/μL) and platelet (965,000/μL) counts. An abdominal ultrasound showed a large mass with associated lymphadenopathy, prompting further evaluation with contrast-enhanced CT. The scan revealed an avidly enhancing mesenteric mass near the superior mesenteric artery with minimal ascites and inguinal lymphadenopathy. The patient underwent laparotomy, during which a highly vascular mass originating from the sigmoid colon was resected, followed by colocolic anastomosis. Histopathological examination identified an intermediate-grade inflammatory myofibroblastic tumor with focal mucosal infiltration. Immunohistochemical staining confirmed the diagnosis, showing positivity for vimentin, smooth muscle actin, and focal desmin. Postoperatively, the patient recovered well, tolerated oral intake by day three, and was discharged on day six after a blood transfusion. At follow-up, he remained asymptomatic, with no recurrence on ultrasound and normalized hemoglobin levels. Conclusion: IMT can occur in the gastrointestinal tract in children. Complete surgical resection is curative.